Risiko Keuangan, Dewan Komisaris, Dewan Direksi dan Kinerja Keuangan Bank Perkreditan Rakyat - Ningrum, Ni Putu Pradina Mas Jaya; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 32 No 1 (2022)DO - 10.24843/EJA.2022.v32.i01.p08, 2022)
The purpose of this study was to obtain empirical evidence of the effect of financial risk, the board of commissioners, and the board of directors on the financial performance of rural banks. This research was conducted at the Rural Bank (BPR) Badung Regency. The method of determining the sample used is purposive sampling. The number of samples taken was 31 BPRs with 2 years of observation so that there were 62 observations. The analysis technique used is multiple linear regression. Based on the results of the analysis, it was found that credit risk, liquidity risk, and operational risk have a negative effect on financial performance, while the board of commissioners and the board of directors have a positive effect on financial performance. This shows that the increasing credit risk, liquidity risk, and operational risk will reduce financial performance, while the greater the number of the board of commissioners and the board of directors, the more will control and supervise the company in meeting financial performance. Keywords : Financial Performance; Financial Risk; Board of Commissioners; Board of Directors, BPR.